A survey of hypertension prevalence, awareness, treatment, and control in health screening camps of rural central Punjab, Pakistan - Salman T. Shafi; Tahir Shafi (Springer, 2019)
Hypertension is a global public health problem with increasing prevalence. There is limited updated information on the prevalence of hypertension in the Pakistani population. This is a cross-sectional study based on data collected during multiple health screening camps held at multiple locations in rural central Punjab, Pakistan in the period between 2008 and 2015. A total of 13,722 patients were included in this study. Crude prevalence of hypertension was 35.1% and age-standardized prevalence was 34.4%. Among patients with hypertension, 62.3% were aware of having high blood pressure; among these patients, 75.3% were already on treatment for hypertension. Blood pressure was controlled in 22.3% of all patients with hypertension. Among those on treatment for hypertension, blood pressure was controlled in 32.3%. Nearly one-third of patients in health screening camps of rural central Punjab had hypertension. Blood pressure control rate was poor among these patients.